Human-Animal Conflict in Jaimini Municipality, Baglung, Nepal - Panta, Saroj Raj (International Research Journal of MMC, 2024)
This study examines the factors that lead to conflict between people and animals in the Jaimini Municipality of Baglung Nepal with an emphasis on how shifting economic conditions impact livestock and agriculture. In terms of agricultural loss livestock depredation and human causation this study sought to explore the conflict between humans and wildlife. It also aims to comprehend local perspectives tolerance and compensation levels as well as the causes of losses brought by wild animals. Both qualitative and quantitative methods were employed in the study including focus groups semi-structured interviews, questionnaire, surveys and case studies. The findings indicated that the most significant harm caused by human animal conflict (HAC) was crop damage with animal attacks on settlements being more common in areas near forests. There was no discernible difference in the amount of damage caused by elephants to various socioeconomic classes making property damage the second most frequent problem encountered by the locals. The results imply that since humans want to rule over and take advantage of nature and animals they are to blame for the conflict. Anger and negativity are common reactions from victims of animal abuse. Problems with migration dependency and brain drain have resulted from the conflicts detrimental effects on the livelihoods of the local population. The study evaluated stakeholders' capacity to reduce human-wildlife conflicts which are mostly caused by mishandling community forests and problems with their applications. Policymakers practitioners, researchers can benefit from its insights into the intricate relationships between people animal's migration and social transformation.